Leadership Effectiveness in Improving The Professionalism of Madrasah Aliyah Teachers in Bengkulu - Bandit Aroman; Khairiah Khairiah (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Teachers still create difficulties in improving professionalism, it can be seen that teacher professionalism is not optimal, certification policies have not improved teacher professionalism, teacher qualifications in carrying out duties are still low, teacher preparation in the teaching process is still not steady, less use of media and learning resources, creativity is still low, mastery of science and technology is still lacking, teachers lack creativity in teaching because it is not in their field. The purpose of this study is to map and analyze the effectiveness of leadership in improving the professionalism of Madrasah Aliyah Bengkulu teachers.Using descriptive qualitative methods. Data sources from scientific books, scientific articles, scientific journals both print and online, both nationally and internationally. The results showed that in developing teacher professionalism, leadership has provided guidance, direction, supervision and provided opportunities for teachers to attend training or trainings, include teachers in certification programs, provide opportunities to continue their studies, collaborate with other institutions / agencies, and carry out visits to other schools. So that professional teachers master the ins and outs of education and teaching and other sciences, teachers also get special education to become teachers who have special skills or expertise, and have competence. Thus it can be concluded that leadership effectiveness can improve teacher professionalism, so it can be recommended to improve teacher professionalism, thereby increasing the effectiveness of Aliyah madrasah leadership in Indonesia.Keywords: Effectiveness, Leadership, Teacher Professionalism, Madrasah Aliyah Abstrak: Guru masih menciptakan kesulitan dalam meningkatkan profesionalitas, hal ini terlihat sikap profesionalitas guru belum optimal, kebijakan sertifikasi belum ada peningkatan profesionalitas guru, kualifikasi guru dalam melaksanakan tugas masih rendah, persiapan guru dalam proses pengajaran masih kurang mantap, kurang memanfaatkan media dan sumber belajar, kreativitas masih rendah, penguasaan ilmu dan teknologi masih kurang, guru kurang kreatifitas dalam mengajar karena bukan pada bidangnya. Tujuan penelitian ini untuk memetakan dan menganalisis efektivitas kepemimpinan dalam meningkatkan profesionalitas guru Madrasah Aliyah Bengkulu.Menggunakan metode kualitatif deskriptif. Sumber data dari buku-buku ilmiah, artikel ilmiah, jurnal ilmiah baik cetak maupun online, baik nasional maupun internasional. Hasil penelitian menunjukkan bahwa dalam mengembangkan profesionalitas guru, kepemimpinan telah memberikan bimbingan, pengarahan, pengawasan dan memberikan kesempatan kepada guru untuk mengikuti diklat atau pelatihan, mengikutkan guru dalam program sertifikasi, memberikan kesempatan melanjutkan studinya, melaksanakan kerjasama dengan lembaga/ instansi lain, serta melaksanakan kunjungan ke sekolah lain. Sehingga guru professional menguasai betul seluk beluk pendidikan dan pengajaran serta ilmu-ilmu lainnya, guru juga mendapatkan pendidikan khusus untuk menjadi guru yang memiliki keterampilan atau keahlian khusus, dan memiliki kompetensi. Dengan demikian dapat disimpulkan bahwa efektivitas kepemimpinan dapat meningkatkan profesionalitas guru, sehingga dapat disarankan untuk meningkatkan profesionalitas guru, maka tingkatkan efektivitas kepemimpinan madrasah Aliyah di Indonesia.Kata kunci: Efektivitas, Kepemimpinan, Profesionalitas Guru, Madrasah Aliyah